Rent extraction amid borrowers’ adversity: evidence from activist short sellers’ attacks - Mensah, Albert Kwame; Kim, Jeong-Bon; Paugam, Luc; Stolowy, Hervé (Review of Finance, 2025)
Abstract Finance theory suggests that the privileged information that traditional banks obtain about borrowers through monitoring creates opportunities for banks to impose informational hold-up costs on such borrowers. Because a surge in borrower risk increases banks’ hold-up power, banks with information monopoly should be able to increase their rates beyond the level explained by borrower risk alone. We test this theory using the setting of activist short sellers’ public allegations—a setting that increases borrower risk and restricts borrower access to public financing sources—and find, on average, that, after controlling for both ex ante and ex post changes in borrower credit risk, banks increase loan pricing following activist short sellers’ allegations. Our loan pricing results not explained by changes in borrower credit risk are consistent with banks extorting borrowers during times of adversity.